2001
DOI: 10.3346/jkms.2001.16.5.603
|View full text |Cite
|
Sign up to set email alerts
|

α-Melanocyte Stimulating Hormone (MSH) decreases cyclosporine A induced apoptosis in cultured human proximal tubular cells

Abstract: The pathogenesis of chronic cyclosporine A (CsA) nephrotoxicity has not been elucidated, but apoptosis is thought to play an important role in CsA induced tubular atrophy. Recently Fas-Fas ligand system mediated apoptosis has been frequently reported in many epithelial cells as well as in T lymphocytes. We investigated the ability of CsA to induce apoptosis in cultured human proximal tubular epithelial cells and also the effect of alpha-MSH on them. Fas, Fas ligand, and an intracellular adaptor protein, Fas-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
(40 reference statements)
1
11
0
Order By: Relevance
“…Since Shihab et al (18) reported induction of the apoptotic gene, Fas, FasL, and p53, in CsA nephrotoxicity, many investigators have reported the mechanism of apoptosis on CsA nephrotoxicity (11,13,14). In this study, we have demonstrated that CsA induced apoptosis in rat renal tubular cells by TUNEL stain.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Since Shihab et al (18) reported induction of the apoptotic gene, Fas, FasL, and p53, in CsA nephrotoxicity, many investigators have reported the mechanism of apoptosis on CsA nephrotoxicity (11,13,14). In this study, we have demonstrated that CsA induced apoptosis in rat renal tubular cells by TUNEL stain.…”
Section: Discussionmentioning
confidence: 64%
“…Most organs undergoing fibrosis will show a paucity of cells, suggesting that apoptosis may be playing an active role in the later stages of fibrosis (10). Our previous studies showed that tubular cell apoptosis can serve as a part of chronic CsA nephrotoxicity and Fas/FasL systems, and their downstream signaling molecules, FADD and PARP cleavages, can mediate apoptotic cell death in cultured renal tubular cells on CsA stimulation, and these findings were alleviated by ␣-melanocyte-stimulating hormone (MSH) treatment (11). ␣-MSH is a proopiomelanocortin derivative and is an endogenous cytokine that suppresses inflammation in various animal models by means of its inhibitory action on proinflammatory cytokines and chemoattractant cytokines (12)(13)(14)(15).…”
mentioning
confidence: 98%
“…This suggests ␣-MSH may affect both the PMN and the endothelial cells. Although an anti-inflammatory and cytoprotective effect of ␣-MSH have been reported also for tubular epithelial cells (10,14),transmigration across HK-2 monolayers was not influenced by ␣-MSH (data not shown), making their importance in ␣-MSH-inhibited migration unlikely. Our data show sequential migration of PMN across endothelial and renal tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 89%
“…␣-Melanocyte-stimulating hormone (␣-MSH), a potent anti-inflammatory peptide, has been shown to be effective in animal models of local and systemic inflammatory disorders, including sepsis syndrome, and inflammatory bowel disease, and acute renal failure (14,17,22). The effects of ␣-MSH are mediated by melanocortin receptors found on macrophages, polymorphonuclear neutrophils (PMN), and renal tubular cells and acts by inhibiting maladaptive activation of genes that cause inflammatory and cytotoxic injury (5,10). However, the effect of ␣-MSH on PMN migration is not known.…”
mentioning
confidence: 99%
“…Acute tubular apoptosis was demonstrated by different techniques in patients with septic AKI, whereas almost no apoptosis was detected in patients with nonseptic AKI. Moreover, in an experimental model of cultured human proximal tubular cells, Jo et al [43] demonstrated that endotoxin, TNF-α and other pro-inflammatory cytokines induced apoptosis of renal proximal tubular cells.…”
Section: Endotoxin Effects In Crs Typementioning
confidence: 99%